Instrumen Penilaian Kemampuan Berpikir Kritis Peserta Didik SMA Negeri Mata Pelajaran Biologi Kelas X - Taufiq Satria Mukti; Edi Istiyono (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret, 2018)
Research development is done by quantitative approach that aims to: (1) Generate tools for the assessment of critical thinking ability; (2) Describe the quality of instruments developed to measure critical thinking skills. The study population is the XIP MIPA class of fourteen SMAN in Kendal District. The sample of the research was determined using purposive sampling technique which represented the school with high, medium, and low ranking criteria. Trial conducted on 201 learners. The test instrument was developed with a reasonable multiple choice form. Four categories of scores on each item correspond to the scoring of the PCM (Partial Credit Model) politomus model. Research data were analyzed using the help of EXCEL application, SPSS 16, QUEST and PARSCALE. The results showed that: (1) The critical thinking test instrument fulfilled the validity of the content of the expert judgment; (2) The test instrument with four categories of fit scores on the PCM model; (3) The test instrument has a high reliability value; (4) The test instrument has good difficulty level criteria; (5) Test instruments can be used to estimate critical thinking skills.